The Cartel Evidence Process: A Review of Business Competition Law in the Case of the Swedish Scania Trucking Company - Dede Kurniasih (Budapest International Research and Critics University, 2022)
This article discusses the issue of cartels in business competition law. The discussion took the case of a cartel carried out by a well-known Swedish truck and bus manufacturer, Scania. In 2017, European Commission member on competition, Margrethe Vestager stated, the European Commission had found that Scania violated EU antitrust rules. The company colluded for 14 years with five other truck manufacturers on pricing trucks and to charge new technology to meet stricter emissions rules. According to the European Commissioner, Scania has been practicing cartels since 1997 and has been going on for 14 years. Scania colluded with five other companies, namely: MAN (Germany), DAF (Netherlands), Daimler (Germany), Iveco (Italy), and Volvo (Sweden)/Renault (France). The case will be discussed using a qualitative method, with discussions on business competition law, cartel theory, and the theory of proof of cartel business competition acts. It is not easy to prove the existence of a cartel and cartel actors can exercise their right not to receive sanctions by appealing and defending their arguments. Solving the cartel, takes a long time and allows developing other problems.